Uses of mosses and lichens in Cerro de la Muerte, Costa Rica (Revista Rupturas, 2024)
The use of mosses and lichens in Cerro de la Muerte, Costa Rica is frequently carried out during the Christmas season, for use in doorways, and the rest of the year as substrates and to make baskets for plants. Despite what is stipulated in the Wildlife Conservation Law and its regulations, excessive extraction of this vegetation occurs, which can affect the decrease in its populations in natural ecosystems such as moors and high-altitude peat bogs, as well as in pastures. The objective is to analyze the marketing chain and the way in which social actors intervene in the use of mosses and lichens, to improve their use and conservation. It was determined that the sale of Mosses and lichens mean an important economic income for the residents of the area, which is why the marketing chain is characterized by “short marketing circuits.” In accordance with the Wildlife Conservation Law and its regulations, it is recommended to continue harvesting and marketing only the moss Leptodontium sp. (pasture wool) on private properties, and not in protected areas, in order to contribute to the conservation of this and other species of mosses and lichens.
Keywords: Leptodontium sp; permit holders; merchants; marketing chain; conservation